#39: Streptococcus anginosus Group Infections in Children: A Retrospective Cohort Study, 2015–2019. (26th March 2021) - Amin, O; Smith, O; Berkowitz, F; Lyon, T; Kao, C; Shane, A; Yildirim, Ia; Gonzalez, M
Abstract: Background: Infections attributed to the Streptococcus anginosus group (SAG), which includes Streptococcus anginosus, Streptococcus constellatus, and Streptococcus intermedius, have varying clinical presentations. SAG infections are difficult to identify initially, and members of the group may require different management strategies. Methods: A retrospective review of SAG-positive cultures from January 2015, to September 2019, was conducted to describe the demographic, clinical, and laboratory features including the site of infection, antibiotic susceptibility, management, and clinical outcome. Results: We identified 561 patients [median age 11.3, interquartile range (IQR) 7.1–14.9 years, male:female ratio 3:2, non-Hispanic–non-Latino 454 (81%), White 279 (49%)]. Thirty-nine (7%) had at least one underlying condition. Of these, inflammatory bowel disease 15 (39%), diabetes 7 (18%), immunodeficiency 5 (13%). SAG was found in exudate, fluid, or aspirate (537/561, 96%), blood (11/561, 2%), and tissue (11/561, 2%) samples; 388 (69%) were polymicrobial infections. The most common site of infection was intra-abdominal (175, 31%), followed by neck/odontogenic (114. 20%) and genitourinary tract (66, 12%). The median length of stay was 6 days (IQR 3–10 days) and was statistically significantly longer for patients with blood, central nervous system, and pulmonary infections compared with soft tissue and upper respiratory tract infections (P < 0.001). Beta-lactams were the most commonly used antibiotics (38%), followed by clindamycin (30 %) (see Figure for antibiotic susceptibility results) and 33 (56%) patients received combination therapy. We did not observe any SAG attributed to mortality. Conclusions: In our retrospective cohort, SAG infections were more commonly identified in males, were associated with abscess formation, and presented as polymicrobial infections. Children with underlying comorbidities are more likely to present with systemic SAG infections. SAG-associated infections can be variable in presentation site and severity and should be considered as pathogens when managing patients.